Development and Validation of a Management of Workplace Violence Competence Scale for Nursing Practicum Students - Dongyan Lu; Sarah Yeun-Sim Jeong; Lingyan Zhu (Elsevier, 2021)
Summary: Purpose: The aim of this study was to develop a scale to measure nursing students' competence in managing violence from patients and relatives in the hospital where nursing students perform clinical practicum. Methods: Literature review and Delphi expert consultation were utilized to develop the content of the management of workplace violence competence scale (MWVCS). A convenience sample of 797 nursing students responded to the questionnaire. Exploratory factor analysis of the scale was performed. Internal consistency and test-retest reliability were examined. Results: The MWVCS consisted of 40 items with a five-point scale. Seven factors explained 63.2% of the total explained variance. The content validity index for the scale was .99. Cronbach's α of the scale was .96, and test-retest correlations were found to be ≥ .76. Conclusion: The MWVCS is a reliable and valid scale for nursing educators to assess the level of students' competence in violence management and to evaluate the effectiveness of education to enhance their ability to manage workplace violence.